To climb or not to climb? Balancing stakeholder priorities at an iconic national park. Issue 2 (3rd April 2018) - Wilson, Erica; Nielsen, Noah; Scherrer, Pascal; Caldicott, Rodney W.; Moyle, Brent; Weiler, Betty
ABSTRACT: In the management of protected areas, stakeholders range from supra-national organisations, through to national and local-level decision-makers. Although there has been substantive research on stakeholders, there is limited inquiry on involving them in the development of nature-based tourism experiences in heavily visited protected areas. Drawing on stakeholder theory, this paper explores stakeholders' perspectives of developing alternative visitor experiences at an iconic mountain, namely the World Heritage listed Wollumbin-Mount Warning National Park in eastern Australia. Due to the popularity of climbing Wollumbin mountain, a number of issues have emerged related to sustainable visitor management, including overcrowding, environmental impacts and Indigenous sensitivities around the climb. Guided by an interpretive methodology, semi-structured interviews were conducted with 22 key 'Wollumbin' stakeholders. Analysis of these interviews revealed that when developing alternative experiences in protected areas, it is important to balance natural and cultural priorities, develop appropriate summit alternatives and overcome tourism resource challenges.